Relationship between Knowledge and Working Period with Compliance with the Use of Pesticide Spray PPE by Farmers in Triyagan Village - Susanto, Agus; Syahrotun Nisa Suratna, Farhana; Sari, Yulia (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
In 2019, there were 147 cases of agricultural pesticide poisoning in Indonesia. Preventing pesticide poisoning requires a high knowledge of personal protective equipment (PPE) and extensive work experience among farmers. This helps farmers become more skilled and aware of the risks, making them more careful and compliant with PPE usage. This study aims to determine the relationship between knowledge and years of service with compliance in using PPE when spraying pesticides. The research is analytical and observational with a cross-sectional design. Respondents were 57 farmers from Triyagan Village, all members of farmer groups. Total sampling was used to select participants. The research instruments included a questionnaire to assess farmers' knowledge and years of service and an observation sheet to evaluate PPE compliance. Data were analyzed using the gamma test and logistic regression. Bivariate analysis with the gamma test revealed a significant relationship between knowledge and years of service with PPE compliance among farmers in Triyagan Village (p = 0.033; r = 0.525; p = 0.037; r = 0.402). Multivariate analysis with logistic regression further confirmed the significant relationship, indicating that knowledge had a greater influence on PPE compliance than years of service (p = 0.033; OR = 3.319; p = 0.037; OR = 1.708). In conclusion, knowledge and tenure are significantly related to PPE compliance among farmers in Triyagan Village. Enhanced knowledge appears to be the critical factor in properly using PPE when spraying pesticides.